2004
DOI: 10.1111/j.0022-202x.2004.22312.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel ABCC6 Mutations in Pseudoxanthoma Elasticum

Abstract: Pseudoxanthoma elasticum (PXE) is a heritable connective tissue disorder caused by mutations in an ABC (ATP-Binding Cassette) transporter gene (ABCC6), which manifests with cutaneous, ophthalmologic, and cardiovascular findings. We studied a cohort of 19 families with PXE, and identified 16 different mutations, nine of which were novel variants. The mutation detection rate was about 77%. We found that arginine codon 518 was, with the previously described R1141X and EX23_29del, a recurrently mutated amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 24 publications
6
82
0
1
Order By: Relevance
“…Performing mutational analysis, we identified 42 different PXE mutations and among these 10 were novel. The frequencies of these mutations were similar to those reported in previous European studies, in which the nonsense mutation p.R1141X and the large deletion Ex23_Ex29del were described as frequent ABCC6 mutations in French, Italian and Dutch PXE patients and most of the further ABCC6 alterations were determined as unique mutations (Chassaing et al, 2004;Gheduzzi et al, 2004;Hu et al, 2004). In contrast to these reports, we found that the splice site mutation c.2787+1G>T is a new recurrent mutation in German PXE families.…”
Section: Novel Pxe Mutationssupporting
confidence: 88%
See 2 more Smart Citations
“…Performing mutational analysis, we identified 42 different PXE mutations and among these 10 were novel. The frequencies of these mutations were similar to those reported in previous European studies, in which the nonsense mutation p.R1141X and the large deletion Ex23_Ex29del were described as frequent ABCC6 mutations in French, Italian and Dutch PXE patients and most of the further ABCC6 alterations were determined as unique mutations (Chassaing et al, 2004;Gheduzzi et al, 2004;Hu et al, 2004). In contrast to these reports, we found that the splice site mutation c.2787+1G>T is a new recurrent mutation in German PXE families.…”
Section: Novel Pxe Mutationssupporting
confidence: 88%
“…In contrast to these reports, we found that the splice site mutation c.2787+1G>T is a new recurrent mutation in German PXE families. The disease-causing mutations p.R518Q and p.R518X that were frequently found in French, Italian and Swiss PXE patients (Chassaing et al, 2004;Gheduzzi et al, 2004;Miksch et al, 2005), rarely occurred in our PXE cohort and were not found in PXE families of Dutch origin . This suggests that the observed heterogeneous distribution of ABCC6 mutations in PXE patients could be due to ethnic or national differences.…”
Section: Novel Pxe Mutationsmentioning
confidence: 60%
See 1 more Smart Citation
“…The most frequent p.R1141X PXE-related allele shared a common haplotype identical-by-descent in seven Italian families homozygous for this mutation. Moreover, comparison of haplotype analyses in Italian and in French PXE families (Chassaing et al, 2004) may suggest the presence of a common ancestor. Our results revealed a distribution of mutations along the ABCC6 gene similar to those published for other European Countries (Le Saux et al, 2001;Hu et al, 2003;Chassaing et al, 2004).…”
Section: Abcc6 Mutationsmentioning
confidence: 99%
“…Recent reports suggest its implication in the cell extrusion of glutathionated metabolites (Belinsky et al, 2002;Ilias et al, 2002). To date, more than 60 causative mutations for PXE have been reported (Hu et al, 2003;Chassaing et al, 2004). Irrespective of the geographic origin of affected individuals, the great majority of mutations have been found between exons 24 and 30 of the ABCC6 gene (Le Saux et al, 2001;Meloni et al, 2001;Pulkkinen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%